2019
DOI: 10.1037/xlm0000703
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic selection does not eliminate attribute amnesia.

Abstract: Attribute amnesia (Chen & Wyble, 2015, 2016) demonstrates that we may not always be able to spontaneously retrieve a simple attribute of a visual object (e.g., its color) for conscious report, even though the object had just been the target in a visual task. Attribute amnesia has been suggested to reflect a lack of consolidation of the task-irrelevant attribute in visual working memory. Here we tested whether saccadic selection eliminates or attenuates attribute amnesia. Saccade targets have been shown to be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…Note that "validity" refers to the between-subjects variable "validity on surprise trial" (i.e., the different rows do not reflect performance on valid vs. invalid pre-or post-surprise trials, but show the proportion of participants with a correct response in the respective group) the Bayes factors suggested only weak evidence in favor of a difference between the surprise and the first post-surprise trial. Numerically, around 60% of participants were correct on the surprise trial, which is a slightly higher percentage than typically observed in attribute amnesia studies (Born et al, 2019;Chen & Wyble, 2015Jiang et al, 2016;Swan et al, 2017), but roughly corresponds to the percentage of participants being able to report the irrelevant information in the studies by Eitam and colleagues (Eitam et al, 2015;Eitam et al, 2013). It is possible that the effect was attenuated by the cue, for instance by providing an alerting signal that may automatically activate attentional resources (possibly irrespective of location).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Note that "validity" refers to the between-subjects variable "validity on surprise trial" (i.e., the different rows do not reflect performance on valid vs. invalid pre-or post-surprise trials, but show the proportion of participants with a correct response in the respective group) the Bayes factors suggested only weak evidence in favor of a difference between the surprise and the first post-surprise trial. Numerically, around 60% of participants were correct on the surprise trial, which is a slightly higher percentage than typically observed in attribute amnesia studies (Born et al, 2019;Chen & Wyble, 2015Jiang et al, 2016;Swan et al, 2017), but roughly corresponds to the percentage of participants being able to report the irrelevant information in the studies by Eitam and colleagues (Eitam et al, 2015;Eitam et al, 2013). It is possible that the effect was attenuated by the cue, for instance by providing an alerting signal that may automatically activate attentional resources (possibly irrespective of location).…”
Section: Discussionmentioning
confidence: 74%
“…As mentioned, based on previous results (Born et al, in 2019;Chen & Wyble, 2015, we had not expected an asymmetry between color and shape (but see Rock et al, 1992). Note also that in other studies with comparatively simple color pop-out displays, the majority of participants were not able to indicate the last target color in a surprise question (Born et al, 2019;Chen & Wyble, 2015). In these studies, the target was likewise presented parafoveally and the presented distractors were either black or gray, such that on each trial, the target was the only colored object.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations